Evaluation of Two Different Solvents for Azolla pinnata Extracts on Chemical Compositions and Larvicidal Activity against Aedes albopictus (Diptera: Culicidae). (13th November 2018) - Ravi, Rajiv; Husna Zulkrnin, Nor Shaida; Rozhan, Nurul Nadiah; Nik Yusoff, Nik Raihan; Mat Rasat, Mohd Sukhairi; Ahmad, Muhammad Iqbal; Hamzah, Zulhazman; Ishak, Intan H.; Mohd Amin, Mohamad Faiz
Abstract : Limited success for Aedes control program has impelled the necessities for new insecticide search. Hence, alternative plant compounds may be competent to overcome the pesticide resistance problem and to lead a chemical-free environment. Following go-green conceptions, larvicidal effects of the Azolla pinnata extracts using methanol and acetone solvent against Aedes albopictus late 3rd instar larvae were evaluated. The A. pinnata fresh plant from Kuala Krai, Kelantan, Malaysia (5° 31′ N 102° 12′ E) was used for crude extraction with Soxhlet apparatus using methanol and acetone solvents. Next, larvicidal test following WHO guidelines was tested against late 3rd instar to early 4th instar larvae of Ae. albopictus mosquitoes. Meanwhile, the chemical composition of extracts and their structures have been identified using GCMS-QP2010 Ultra (Shimadzu) fitted with Rtx-5MS capillary column (30 m × 0.25 mm inner diameter, ×0.25 μ m film thickness; maximum temperature, 370°C), coupled to QP2010 Ultra (Shimadzu) MS. Results of methanol solvent showed the highest larvicidal activity against late 3rd instar to early 4th instar Ae. albopictus larvae with LC50 and LC95 values of 867 ppm and 1293 ppm at 24 hours, respectively, and 647 ppm and 972 ppm at 48 hours, respectively. Meanwhile, acetone solvent compounds were recorded with LC50 and LC95 values of 1072 ppm and 1302 ppm at 24 hours, respectively, and 904 ppm and 1126 ppm at 48 hours, respectively. Finally, the chemical composition of A. pinnata plant extracts has been characterized for 35 active compounds from methanol solvent and 37 active compounds with acetone solvent. In conclusion, A. pinnata plant bioactive molecules are efficient and could be developed as an eco-friendly, "go-green" approach for mosquitoes' larvicidal control programs. Thus, our study suggests that future research can be conducted on A. pinnata bioactive ingredients against Ae. albopictus larvae in small-scale field trials as botanical insecticide for environmentally friendly approach.